MORNING IN FINDING IN PROMOTING A HEALTHY LIFESTYLE IMPORTANCE OF GYMNASTICS (Neo Science Peer Reviewed Journal, 2023)
In the article, morning gymnastics is used to determine a healthy lifestyle The importance of morning physical training is given as an example.